Development of Liposomal Gel for Transdermal Delivery of Selegiline - R, Megha (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACTThe aim of present study was to developed liposomal gel of Selegiline to deliver the active substance at targeted organ with maximum therapeutic effect. Liposomes are concentric bilayered vesicles in which an aqueous volume is entirely enclosed by a membranous lipid bilayer mainly composed of natural or synthetic phospholipids. Liposome gels were prepared by incorporation of liposomes into a structured vehicle. Liposome gels provided a prolonged drug release rate. The concentration of the gelling agent affected the release rate slightly. Selegiline is a drug used for the treatment of early-stage Parkinson’s disease, depression and senile dementia. In normal clinical doses it is a selective irreversible Monoamine oxidase inhibitor-B inhibitor. Transdermal delivery of Selegiline by encapsulation into liposome in the form of gel in order to improve the bioavailability following oral administration by avoiding hepatic metabolism. This study achieve maximum therapeutic effect and to have sustained release of drug through enhancing circulations life time.